2010
DOI: 10.1088/0004-637x/725/1/188
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATED WOLF–RAYET STARS AND O SUPERGIANTS IN THE GALACTIC CENTER REGION IDENTIFIED VIA PASCHEN-α EXCESS

Abstract: We report the discovery of 19 hot, evolved, massive stars near the Galactic center region (GCR). These objects were selected for spectroscopy owing to their detection as strong sources of Paschen-α emission-line excess, following a narrowband imaging survey of the central 0. • 65 × 0. • 25 (l, b) around Sgr A * with the Hubble Space Telescope. Discoveries include five carbon-type (WC) and six nitrogen-type (WN) Wolf-Rayet stars, six O supergiants, and two B supergiants. Two of the O supergiants have X-ray coun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(145 citation statements)
references
References 61 publications
3
141
1
Order By: Relevance
“…This means that a small percentage, about 5%, of high mass stars may form in isolation, in very good agreement with the finding by Parker & Goodwin (2007). Even in the Galactic center region, a number of Wolf-Rayet stars and O supergiants might have formed in isolation (Mauerhan et al 2010). Lamb et al (2010) observed eight apparently isolated O stars in the SMC.…”
Section: Discussionsupporting
confidence: 81%
“…This means that a small percentage, about 5%, of high mass stars may form in isolation, in very good agreement with the finding by Parker & Goodwin (2007). Even in the Galactic center region, a number of Wolf-Rayet stars and O supergiants might have formed in isolation (Mauerhan et al 2010). Lamb et al (2010) observed eight apparently isolated O stars in the SMC.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, the discovery we present below is carried out through observations in the Paschen-α line that were initially aimed at finding hot massive evolved cluster members. P α observations have been already proven to be very effective to find such stars in clusters (Davies et al 2012a,b) or in the central region of the Milky Way (Mauerhan et al 2010a;Dong et al 2011), however this method has never been used to locate lower luminosity emission-line objects like FS CMa stars.…”
Section: Introductionmentioning
confidence: 99%
“…Because P100 and P107 are relatively older than the Arches cluster (Dong et al, in preparation), future proper motion are needed to confirm their relationship. Combined with three WNh stars within 1-2 pc of the Arches cluster suggested by Mauerhan et al (2010), there are five 'field' EMSs which could have been ejected from the Arches cluster.…”
Section: The Origin Of Paschen-α Emitting Sourcesmentioning
confidence: 99%